ANALISIS PELATIHAN, PEMBERDAYAAN DAN KEPUASAN KERJA PEGAWAI DI PT BANK RAKYAT INDONESIA KANTOR CABANG KUNIINGAN - Putri, Wulan Dewani; NURYANTI, B LENA; Masharyono, Masharyono (Journal of Business Management Education (JBME), 2018)
Purpose - The purpose of this study is to analyze empowerment training and job satisfaction.The design / methodology / approach - The design of this study was cross sectional. This research uses descriptive approach with explanatory survey method. The employee analysis unit is 50 people. Data collection using questionnaire. The analysis technique used is descriptive technique by using frequency distributionFindings – Based on the results of research using descriptive analysis, the results obtained that training in the good category, empowerment in the good category, and job satisfaction in the high category.Originality - This study provides a basis for understanding the issues of the training and empowerment on job satisfaction. The difference of this research with previous research is on the object in PT. Bank Rakyat Indonesia Kuningan branch office, training variable, empowerment and job satisfaction, and references used by researchers with previous researchers.